ANALISIS MANAJEMEN DAN INTERVENSI BAGI PASIEN TERHADAP UPAYA PROMOSI KESEHATAN RUMAH SAKIT (PKRS) DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN TAHUN 2012 - lukman hakim; heldi BZ; fauzi bowo (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract Analysis Of Management and Patient Intervention For Effort Of Health Promoting Hospital (HPH) Of H. Adam Malik Medan General Hospital Center in 2012. Nowadays, reorientation of hospital’s services is not only oriented to curative and rehabilitative, while also prioritizing preventive and promotive aspects to be a health promoter hospital. The research was  a qualitative study  that analyzed  the implementation of health promotion of  H. Adam Malik Medan General Hospital based on WHO standard on the standard of hospital as health promoter that compliance the  management policy aspects and intervention to the patient in health promoter  aspects. The research was applied indepth interview, observation and document study as data collection tools. The research indicated that  H. Adam Malik Medan General Hospital  had fulfill the standard of WHO on health promotion hospital. The  policy comitment aspect of H. Adam Malik Medan General Hospital had be realized in a strategic plan such as  annual work plan. Quantitatively  the human resources  was sufficient, but qualitatively it needs to improve the quality through training of existing health promotion hospital. The budget had be included in the budget of  H. Adam Malik Medan General Hospital. The facilities and infrastructure was good qualitatively, but  quantitatively it must be increase. The documentationof intervention had implemented routinely. The evaluation was also conducted in  monthly or annually meeting. The point of patient intervention, the assessment on health promotion requirement for the patient need was implemented since the patient obtain the first service through the medical record of health history of patient. The access of information about health promotion  for the patient had be presented either verbally or in written form, also presented in audio and visual.